Preheating axions in string cosmology - Leedom, Jacob M.; Putti, Margherita; Righi, Nicole; Westphal, Alexander (The journal of high energy physics, 2025)
A bstract Certain inflationary models can feature periods of preheating — an era preceding reheating during which parametric resonance triggers an exponential production of bosons. This non-perturbative process can have significant impact on the history of our universe, with consequences ranging from altered reheating channels to overproduction of dark radiation to overclosure. In this work, we study parametric resonance production of axions in string models of inflation. We find that the kinetic couplings and moduli-dependent axion masses give rise to generalizations of the Mathieu equation. We study these generalizations and determine the strength of parametric resonance created by such couplings. We then apply this technology to fibre inflation models in Type IIB orientifold compactifications. We find that heavy axions can be copiously produced and avoidance of overclosure results in constraints on the typical fibre inflation parameter space.